Employment of Digital Media to Increase the Self-Efficiency of Young Smokers - Lismayanti, Lilis; Fitriani, Ade; Sukmawati, Ima; Herlina, Lily; Yunitri, Ninik; Anwar, Syamsul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Smoking is a habit or behavior that is very difficult to quit, especially for adolescents. To be able to stop smoking behavior, a strong belief (self-efficacay) is needed from the adolescent to stop smoking. The aim of this study is to determine the effect of empowerment through digital media on the self-efficacy of adolescent smokers at Senior High School. Method This study used a quasi-experimental design through a group pre-test and post-test design. The sampling technique was through convenience sampling, which amounted to 28 respondents. Collecting research data using the SEQ 12 (Smoking Self-Efficacy Questionaire) questionnaire instrument given at the pre-test and post-test stages. The collected data is then analyzed, which includes univariate analysis, namely analysis of demographic data and bivariate analysis to determine the effect of empowerment using digital media on the self-efficacy of adolescent smokers at SMA Negeri 2 Ciamis using the Wilcoxon test because the normality test results show abnormal data distribution. The results of the Wilcoxon test with a p-value of 0.002 <0.05, which means that there is a significant effect of empowerment using digital media on the self-efficacy of adolescent smokers at Senior High School. The conclusion based on the research that has been done is that empowerment with digital media has an effect on increasing the self-efficacy of adolescents to quit smoking.